A Systematic Examination of the Influence of Indicators of Mental Illness on Deaths in the Texas Criminal Justice System - Pollock, Wendi K. (Criminal justice review, 2023)
The publicized deaths of individuals such as Sandra Bland raise questions about whether, and how, the American criminal justice system should handle individuals who display symptoms of mental illnesses. The current study seeks to establish whether there is a stage in the criminal justice process at which the presence of an indicator of a mental illness represents a particularly high risk of death in custody. Using multilevel logistic regression and data on 10,667 civilian deaths that occurred in the custody of criminal justice agencies across the state of Texas, from January 1st, 2005, through October 30th, 2020, results suggest that indicators of mental illness represent the highest risk of death when an individual is in the custody of police. At later stages in the criminal justice system process, particularly jail and prison, indicators of a mental illness reduce the chances that someone will die in custody. Policy implications are discussed.